Shear-Induced Nucleation and Growth in Isotactic Polypropylene - Pantani, Roberto; Coccorullo, Ivano; Volpe, Valentina; Titomanlio, Giuseppe (Macromolecules, 2010)
The possibility of controlling the final morphology, and thus the resulting mechanical and functional properties, of semicrystalline polymers based on the study of polymer crystallization stimulated by flow is highly intriguing. Recent advances in experimental techniques that allow in situ measurements of material morphology under deformation have escalated research in this subject area. However, despite of the huge efforts spent, the description of the evolution of morphology under shear conditions is still challenging and even the basic principles of the phenomenon are not well understood yet. In this work, experiments of nucleation density and growth rate of spherulites were carried out under continuous shear in a range of temperature (138−144 °C) and shear rate (0−0.30 s−1) which, although narrow in absolute, can be considered quite wide taking into account the experimental difficulties presented by this kind of tests. Collected data were analyzed with the aim of determining scaling rules which can describe the effect of flow on crystallization kinetics. It was found that a proportionality exists between nucleation rate and spherulitic growth rate under flow, suggesting that whatever the controlling mechanism for the enhancement of nucleation rate is, it has a similar effect also on growth rate. The effect of flow on nucleation and growth rates was attributed to the increase of the melting temperature due to flow. In turn, the melting temperature estimated for the tests conducted in the whole range of temperatures and shear rates was found to be dependent on the Weissenberg number.